Cointegration in equity markets: a comparison between South African and major developed and emerging markets - Petrov, Pavel (Rhodes University, Faculty of Science, Department of Statistics, 2011)
Cointegration has important implications for portfolio diversification. One of these is that in order to spread risk it is advisable to invest in markets that are not cointegrated. Over the last several decades communication technology has made the world a smaller place and hence cointegration in equity markets has become more prevalent. The bulk of research into cointegration focuses on developed and Asian markets, with little research been done on African markets. This study compares the Engle-Granger and Johansen tests for cointegration and uses them to calculate the level of cointegration between South African and other global equity markets. Each market is compared pair-wise with South Africa and the results have been that in general South Africa is cointegrated with other emerging markets but not really with African nor developed markets. Short-run analysis with the error correction was carried out and showed that in general markets respond slowly to any disequilibrium. Innovation accounting methods showed that the country placed first in Cholesky ordering dominates the other one. Multivariate cointegration was carried out using three selections of 4, 6 and 8 market portfolios. One of the markets was SA and the others were all chosen based on the criteria that they are not pair-wise cointegrated with SA. The level of cointegration varied depending on the portfolios, as did the error correction rates, impulse responses and variance decomposition. The one constant was that the USA dominated any portfolio where it was introduced. Recommendations were finally made about which market portfolio an investor should consider as most favourable.
Keywords: Cointegration; Stock exchanges -- South Africa; Stock exchanges -- Developing countries; Stock exchanges -- Developed countries -- South Africa -- Economic conditions; Portfolio management -- South Africa; Econometrics; Autoregression (Statistics)